Mass spectrometry-based identification of bacteria isolated from industrially contaminated site in Salamanca (Mexico) and evaluation of their potential for DDT degradation - Garcia Lara, Bianey; Wrobel, Katarzyna; Corrales Escobosa, Alma Rosa; Serrano Torres, Oracio; Enciso Donis, Israel; Wrobel, Kazimierz (Folia microbiologica, 2021)
Longstanding industrial deposits of 1-chloro-4-[2,2,2-trichloro-1-(4-chlorophenyl)ethyl]benzene (DDT) impose environmental threat in Salamanca city, located in central Mexico. Native bacteria from this location were isolated and identified, and their potential utility for DDT biodegradation was examined. Twenty-five isolates were obtained, and cell lysates were analyzed by matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) with BiotyperTR; twenty-one organisms were identified at species level, and the other four were assigned to genus. The most abundant species corresponded to Bacillus (44%) and Pseudomonas genera (20%). Eight bacteria could grow in the presence of 200 mg/L of DDT. Two-week exposure of Lysinibacillus fusiformis, Bacillus mycoides, Bacillus pumilus, and Bacillus cereus to DDT 50 mg/L and 200 mg/L, caused percentage pesticide degradation in the range 41-48% and 26-31%, respectively. Other four bacteria presented lower degradation rates. Gas chromatography-mass spectrometry (GC-MS) analysis of the spent media revealed that eight isolates assisted the conversion of DDT, DDD (1,1-dichloro-2,2-bis-(4-chlorophenyl)ethane), and DDE (1,1-dichloro-2,2-bis-(4-chlorophenyl)ethylene) to DDMU (1,1-(2-chloro-1,1-ethenediyl)-bis-(4-chlorobenzene)); however, DDNU (2,2-bis(4-chlorophenyl)ethylene), DBP (4,4'-dichlorobenzophenone(bis(4-chlorophenyl)methanone)) and DBH (bis(4-chlorophenyl)methanol) were found only for L. fusiformis, B. mycoides, B. cereus, B. marisflavi, and B. megaterium. Within the context of DDT biodegradation, the first three were the most promising isolates and further studies will be aimed at setting the experimental conditions for efficient mineralization of DDT congeners.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; DDT; Mexiko; Bacillaceae; Biodegradation, Environmental; Bacillus; látky znečišťující životní prostředí; biodegradace; Bacteria; Environmental Pollutants; Mexico; mikrobiologie životního prostředí; Environmental Microbiology